2020
DOI: 10.1038/s41409-020-0981-7
|View full text |Cite|
|
Sign up to set email alerts
|

ABO incompatibile graft management in pediatric transplantation

Abstract: Up to 40% of donor-recipient pairs in SCT have some degree of ABO incompatibility, which may cause severe complications. The aim of this study was to describe available options and survey current practices by means of a questionnaire circulated within the EBMT Pediatric Diseases Working Party investigators. Major ABO incompatibility (donor's RBCs have antigens missing on the recipient's cell surface, towards which the recipient has circulating isohemagglutinins) requires most frequently an intervention in case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…There was no significant difference between the two groups in OS nor EFS in the entire cohort (Figure 3), and TRM in a separate match‐paired analysis in the groups of patients with malignant versus non‐malignant diseases (data not shown). In light of recently published work, 16 we separately investigated the outcomes (OS, EFS and TRM) in recipients with higher (≥16) versus lower (0–8) anti‐donor ABO titres, which were indistinguishable (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no significant difference between the two groups in OS nor EFS in the entire cohort (Figure 3), and TRM in a separate match‐paired analysis in the groups of patients with malignant versus non‐malignant diseases (data not shown). In light of recently published work, 16 we separately investigated the outcomes (OS, EFS and TRM) in recipients with higher (≥16) versus lower (0–8) anti‐donor ABO titres, which were indistinguishable (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Alternative methods for management of ABO major incompatible BM transplantation have been proposed. According to a recent survey of Balduzzi et al 16 for the EBMT Pediatric Working Party, our approach is not a preferred method in the majority of transplant centres, which identified especially RBC depletion from the graft and plasma exchange as most relevant. While both methods are well established and clearly effective with respect to their immediate goal of rendering infusion of the transplant acutely safe and tolerable, both are also associated with relevant disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since various donor sources including cord blood have been used in recent years, the influence of donor sources on ABO‐incompatible HSCT recovery may be of concern. In addition, research on erythropoiesis has shown that ABO incompatibility delays erythrocyte engraftment or presents a risk for developing pure red cell aplasia (PRCA) 2,4,6,8,11,12 . However, the specific types of ABO‐incompatible HSCTs that cause delayed erythrocyte engraftment are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In ABO incompatibility, there are three different patterns—major mismatch, minor mismatch, and bidirectional mismatch—depending on the combination of recipient and donor ABO blood types 1,4,12 . In major mismatch and bidirectional mismatch, an anti‐A/B isoagglutinin directed against the donor's A/B antigen on erythrocyte is present in the recipient 1,4 .…”
Section: Introductionmentioning
confidence: 99%